In vivo cell type-specific CRISPR knockdown of dopamine beta hydroxylase reduces locus coeruleus evoked wakefulness - Hiroshi Yamaguchi (Nature Portfolio, 2018)
Neurons of the locus coeruleus (LC) are implicated in attention and arousal. Here the authors use CRISPR/Cas9 to disrupt dopamine beta hydroxylase in LC neurons and see this reduces LC-evoked sleep-to-wake transitions and wake length.